Sinus Floor Augmentation—Associated Surgical Ciliated Cysts: Case Series and a Systematic Review of the Literature - Adrian Kahn; Shlomo Matalon; Rahaf Bassam Salem; Lazar Kats; Liat Chaushu; Marilena Vered; Eyal Rosen (Applied Sciences, 2021)
This study aimed to characterize the demographic and clinical features of underreported surgical ciliated cysts developing after sinus floor augmentation, based on a series of cases from our files and a systematic review of the literature. A series of five cases (four patients) of microscopically confirmed surgical ciliated cysts following sinus floor augmentation procedures from our files are described. A systematic literature search (1991–2020) with strict clinical-, radiological- and microscopic-based exclusion and inclusion criteria was performed to detect additional similar cases. The systematic review revealed only five cases that fulfilled the inclusion criteria. Altogether, surgical ciliated cysts associated with sinus floor augmentation have been rarely reported in the literature, and have not been characterized either demographically or clinically. Graft materials were diverse, implants were placed simultaneously, or up to two years post-augmentation. The associated surgical ciliated cysts developed between 0.5 and 10 years post-augmentation. Although limited in its extent, this study is the first series to characterize possible underreported sequelae of surgical ciliated cysts associated with sinus floor augmentation. It emphasizes the need for long post-operative follow-up and confirmation of lesion by microscopic examination.